PENGEMBANGAN DESAIN PEMBELAJARAN SPLDV BERBASIS PBL UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP - muyassar a'la; I Made Arnawa (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
The difficulty of educators in designing interesting learning paths for students makes students tend to lack understanding of mathematics. The learning flow used tends to ask students to remember the "ways" they teach in solving problems rather than stimulating knowledge. As a result, the knowledge gained by students is less meaningful and quickly forgotten. Therefore, a learning design for the topic of a system of two-variable linear equations (SPLDV) based on Problem Based Learning (PBL) was developed in class VIII SMP that is valid, effective and practical.This research was carried out by combining two types of design research, namely the design model development of Tjeerd Plomp and Gravemeijer & Cobb. To implement LIT, educator books and student books use the Plomp research design. Furthermore, for the development of learning flow, it was designed using Gravemeijer and Cobb's research design. The learning design is focused on students' mathematical communication skills on SPLDV topics. Design trials were carried out in one-to-one evaluations and small group evaluations. Data were obtained from student response questionnaires, educator response questionnaires, and field notes.The results showed that the learning design for the SPLDV topic with the PBL approach through educator books and student books was valid, effective and practical. It is said to be valid because it has fulfilled the validity characteristics both in terms of content and construct. It is said to be effective because it can improve students' mathematical communication skills. It is said to be practical because this product is easy to use and understand, the allotted time is very efficient, very interesting and contributes to SPLDV learning.